Safety netting advice for respiratory tract infections in out-of-hours primary care: A qualitative analysis of consultation videos. Issue 1 (31st December 2022) - Colliers, Annelies; Philips, Hilde; Bombeke, Katrien; Remmen, Roy; Coenen, Samuel; Anthierens, Sibyl
Abstract: Background: General practitioners (GPs) use safety netting advice to communicate with patients when and how to seek further help when their condition fails to improve or deteriorate. Although many respiratory tract infections (RTI) during out-of-hours (OOH) care are self-limiting, often antibiotics are prescribed. Providing safety netting advice could enable GPs to safely withhold an antibiotic prescription by dealing both with their uncertainty and the patients' concerns. Objectives: To explore how GPs use safety netting advice during consultations on RTIs in OOH primary care and how this advice is documented in the electronic health record. Methods: We analysed video observations of 77 consultations on RTIs from 19 GPs during OOH care using qualitative framework analysis and reviewed the medical records. Videos were collected from August until November 2018 at the Antwerp city GP cooperative, Belgium. Results: Safety netting advice on alarm symptoms, expected duration of illness and/or how and when to seek help is often lacking or vague. Communication of safety netting elements is scattered throughout the end phase of the consultation. The advice is seldom recorded in the medical health record. GPs give more safety netting advice when prescribing an antibiotic than when they do not prescribe an antibiotic. Conclusion: We provided a better understanding of how safety netting is currently carried out in OOH primary care for RTIs. Safety netting advice during OOH primary care is limited, unspecific and not documented in the medical record.